The Prognostic Role of Hematological Markers in Acute Pulmonary Embolism: Enhancing Risk Stratification - Elena Emilia Babes; Andrei-Flavius Radu; Victor Vlad Babeş; Paula Ioana Tunduc; Ada Radu; Gabriela Bungau; Cristiana Bustea (Medicina, 2025)
Background and Objectives: Assessing risk is essential for optimal care in acute pulmonary embolism (PE). The present research seeks to evaluate the value of admission blood cellular indices as predictors of in-hospital outcome in acute PE and their utility in conjunction with validated risk tools such as the Pulmonary Embolism Severity Index (PESI) score and the European Society of Cardiology (ESC) risk stratification. Materials and Methods: A total of 1058 individuals hospitalized at Bihor County Emergency Hospital, Oradea, Romania, with a diagnosis of acute PE confirmed by contrast-enhanced computed tomographic pulmonary angiography were retrospectively evaluated. Results: A total of 165 patients (18.2%) experienced adverse outcomes, including in-hospital mortality, cardiac arrest, cardiogenic shock, or persistent hypotension, and required rescue thrombolytic therapy. The neutrophil-to-lymphocyte ratio (NLR) was an independent predictor for in-hospital adverse outcome OR = 1.071 (95% CI 1.01–1.137), p < 0.001. NLR as a predictor of adverse outcome had an AUC of 0.712 (95% CI 0.661–0.742), p < 0.001, sensitivity of 72.56%, and specificity of 64.19% for a cutoff value of >5.493. In a combined model with PESI or with ESC risk classification, NLR is leading to a significant improvement in their AUC (p < 0.001). Conclusions: Among hematological markers, NLR holds the greatest relevance for stratifying risk in acute pulmonary embolism and serves as an independent indicator of unfavorable in-hospital prognosis. NLR had an acceptable discriminative power to predict short-term complications and can increase the predictive value of the PESI score and of ESC risk classification.